Kajian Bentuk dan Makna Leksikon Budi Daya Salak di Desa Aribaya Kabupaten Banjarnegara (Kajian Morfologi) - Salima, Farah Zahrotus; Fateah, Nur (Universitas Muhammadiyah Surabaya, 2024)
The use of Javanese among a group of people who work as snake-fruit farmers is a form of communication created to make it easier in understanding the form and meaning of terms in snake-fruit farming. Each region has its own set of languages that reflects the customs and traditions of its inhabitants. Having a common language facilitates communication and social interactions between members of the community. This study utilizes a qualitative descriptive approach to investigate the form and meaning of the language used by snake-fruit farmers in Aribaya Village, Banjarnegara Regency. The data collection methods employed in this research include case studies, observations, and interviews, with data analysis using Miles and Huberman's interactive model. The findings of the study include the form and meaning of the lingual units used by snake-fruit farmers.